Discovery of N-(6-Methoxypyridin-3-yl)quinoline-2-amine Derivatives for Imaging Aggregated α-Synuclein in Parkinson’s Disease with Positron Emission Tomography - Haiyang Zhao; Tianyu Huang; Dhruva D. Dhavale; Jennifer Y. O’Shea; Zsofia Lengyel-Zhand; Dinahlee Saturnino Guarino; Jiwei Gu; Xuyi Yue; Ying-Hwey Nai; Hao Jiang; Marshall G. Lougee; Vinayak V. Pagar; et al. (Cells, 2025)
The fibrillary aggregation of α-synuclein is a hallmark of Parkinson’s disease (PD) and a potential target for diagnostics and therapeutics. Although substantial effort has been devoted to the development of positron emission tomography (PET) probes for detecting α-synuclein aggregates, no clinically suitable tracer has been reported. The design and synthesis of 43 new N-(6-methoxypyridin-3-yl)quinolin-2-amine derivatives and an evaluation of their α-synuclein binding affinity is reported here. Compounds 7f, 7j, and 8i exhibited high affinity for α-synuclein and were selected for 11C, 18F, 125I, or 3H radiolabeling. A photoaffinity variant, TZ-CLX, structurally related to 7j and 8i, demonstrated preferential binding to the C-terminal region of α-synuclein fibrils. PET brain imaging studies using [11C]7f, [18F]7j, and [11C]8i in non-human primates indicated that these three α-synuclein PET tracers penetrated the blood–brain barrier. Both [11C]7f and [18F]7j showed more favorable brain washout pharmacokinetics than [11C]8i. In vitro binding assays showed that [125I]8i is a very potent α-synuclein radioligand, with Kd values of 5 nM for both PD brain tissues and LBD-amplified fibrils; it is also selective for PD tissues versus AD or control tissues. These results strongly suggest that the PET probes based on the N-(6-methoxypyridin-3-yl)quinoline-2-amine scaffold have potential utility in detecting α-synuclein aggregates in vivo.